2022
DOI: 10.1051/0004-6361/202244048
|View full text |Cite
|
Sign up to set email alerts
|

Finding the birthplace of HMXBs in the Galaxy using Gaia EDR3: Kinematical age determination through orbit integration

Abstract: Context. High-Mass X-ray Binaries (HMXBs) are produced after the first supernova event in a massive binary. These objects are intrinsically young, and can suffer from a significant natal kick. As such, the progenitors of HMXBs are likely to have formed away from the current location of the X-ray emitting systems. Aims. We aim to find the birthplace of the known HMXBs of our Milky Way. Specifically, we want to answer the question whether the formation of HMXBs can be associated to open stellar clusters and/or G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 85 publications
(92 reference statements)
0
4
0
Order By: Relevance
“…The known classifications of the X-ray sources in the XDBS catalog include HMXBs based on Liu et al (2006); Doroshenko et al (2021); Fortin et al (2022) and SIMBAD (Wenger et al 2000), γ Cas analogs (Smith et al 2016;Nazé & Motch 2018;Nazé et al 2020), and young stellar objects (YSOs) classified from SIMBAD if main type is YSO, Orion V*, or Ae*. All other sources are labeled as stars by default, but their true class could still be one of the above.…”
Section: Source Classificationsmentioning
confidence: 99%
“…The known classifications of the X-ray sources in the XDBS catalog include HMXBs based on Liu et al (2006); Doroshenko et al (2021); Fortin et al (2022) and SIMBAD (Wenger et al 2000), γ Cas analogs (Smith et al 2016;Nazé & Motch 2018;Nazé et al 2020), and young stellar objects (YSOs) classified from SIMBAD if main type is YSO, Orion V*, or Ae*. All other sources are labeled as stars by default, but their true class could still be one of the above.…”
Section: Source Classificationsmentioning
confidence: 99%
“…We note that this is likely a lower estimate of the average separation dis- tance between an HMXB and its parent YSC, as the nearest YSC may not be the actual parent cluster to a given HMXB. The HMXB may not have formed in a YSC at all; YSCs are typically surrounded by larger star-forming complexes and/or OB associations which could be the true birth site of the HMXBs, as was found for some Galactic HMXBs (Fortin et al 2022).…”
Section: Resultsmentioning
confidence: 97%
“…Bodaghee et al (2012) considered the spatial (or cross-) correlation function between HMXBs and OB associations in the Milky Way, and found that HMXBs were on average ∼200-400 pc from the nearest OB association (consistent with the natal kick scenario) with a kinematical age since compact object formation of ∼4 Myr. Another recent study by Fortin et al (2022) identified the birthplaces of ∼15 Galactic HMXBs using Gaia (seven of which were YSCs and eight were structures associated with a Galactic spiral arm). However, due to obscuration, only HMXBs out to ∼8 kpc can be robustly detected, and astrometric uncertainties and distance uncertainties in the Galactic disk hinder our ability to form a complete census of HMXBs and their orbital trajectories within the Milky Way.…”
mentioning
confidence: 99%
“…Catalogues of HMXBs have already been used to constrain their properties as a population (see e.g. Coleiro et al 2013 andFortin et al 2022a). HMXBs are also representatives of a source category that is directly related to supernova explosions as well as to compact binaries that finally merge as gravitational wave sources (see a recent review by van den Heuvel 2019).…”
Section: Introductionmentioning
confidence: 99%